Carbon Isotope Fractionation during Aerobic Biodegradation of Trichloroethene by Burkholderia cepacia G4: a Tool To Map Degradation Mechanisms - Barth, Johannes A. C. (American Society for Microbiology, 2002)
The strain Burkholderia cepacia G4 aerobically mineralized trichloroethene (TCE) to CO(2) over a time period of ∼20 h. Three biodegradation experiments were conducted with different bacterial optical densities at 540 nm (OD(540)s) in order to test whether isotope fractionation was consistent. The resulting TCE degradation was 93, 83.8, and 57.2% (i.e., 7.0, 16.2, and 42.8% TCE remaining) at OD(540)s of 2.0, 1.1, and 0.6, respectively. ODs also correlated linearly with zero-order degradation rates (1.99, 1.11, and 0.64 μmol h(−1)). While initial nonequilibrium mass losses of TCE produced only minor carbon isotope shifts (expressed in per mille δ(13)C(VPDB)), they were 57.2, 39.6, and 17.0‰ between the initial and final TCE levels for the three experiments, in decreasing order of their OD(540)s. Despite these strong isotope shifts, we found a largely uniform isotope fractionation. The latter is expressed with a Rayleigh enrichment factor, ɛ, and was −18.2 when all experiments were grouped to a common point of 42.8% TCE remaining. Although, decreases of ɛ to −20.7 were observed near complete degradation, our enrichment factors were significantly more negative than those reported for anaerobic dehalogenation of TCE. This indicates typical isotope fractionation for specific enzymatic mechanisms that can help to differentiate between degradation pathways.